Pengaruh Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan Yang Terdaftar Di Jakarta Islamic Index (Jii) Periode 2017 – 2021 - Anggraini Namira Agustin; Maulana Yusuf; Ahmad Syahrizal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of profitability and liquidity on firm value in companies listed on the Jakarta Islamic Index (JII) for the 2017-2021 period. This study uses a quantitative approach and the method used is panel data regression analysis. The sample used in this study was a saturated sample, as many as 9 companies were selected according to the criteria. The results of this study indicate that the Return on Assets variable has no effect on firm value, Return on Equity has no effect on firm value and Current Ratio has no effect on firm value. Meanwhile, simultaneously, the ROA, ROE and CR variables affect the Firm Value (PBV) of companies listed on the Jakarta Islamic Index (JII) for the 2017-2021 period with a coefficient of determination of 71,9%.